2007
DOI: 10.1177/0142723707081653
|View full text |Cite
|
Sign up to set email alerts
|

Do Japanese children say `yes' to their mothers? A naturalistic study of response bias in parent-toddler conversations

Abstract: This study investigated the situations in which children say `yes' in response to yes-no questions. Japanese-speaking children aged 2;0—3;11 ( N=38) were asked yes-no questions by their own mothers at home. Children showed a strong yes bias. The results, combined with those of earlier studies, suggest that a yes bias is a general phenomenon. In addition, young Japanese children showed Japanese-specific response tendencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(61 citation statements)
references
References 16 publications
3
56
2
Order By: Relevance
“…1016/j.jecp.2011.04.012 questions pertaining to various entities such as objects, children's preference for objects, and facial expressions) (e.g., Fritzley & Lee, 2003;, 2010b. These studies found that younger preschoolers consistently exhibited a strong yes bias, but older preschoolers either did or did not exhibit any response bias (Fritzley & Lee, 2003;Okanda & Itakura, 2007, 2010bOkanda, Somogyi, & Itakura, 2011). Given these results, researchers suggested that yes-no questions are not suitable for younger preschoolers (Fritzley & Lee, 2003) or both younger and older preschoolers (Okanda & Itakura, 2010b).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1016/j.jecp.2011.04.012 questions pertaining to various entities such as objects, children's preference for objects, and facial expressions) (e.g., Fritzley & Lee, 2003;, 2010b. These studies found that younger preschoolers consistently exhibited a strong yes bias, but older preschoolers either did or did not exhibit any response bias (Fritzley & Lee, 2003;Okanda & Itakura, 2007, 2010bOkanda, Somogyi, & Itakura, 2011). Given these results, researchers suggested that yes-no questions are not suitable for younger preschoolers (Fritzley & Lee, 2003) or both younger and older preschoolers (Okanda & Itakura, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Okanda and Itakura (2010b) proposed that younger and older preschoolers might exhibit response biases due to different mechanisms. They noted that cognitive abilities such as inhibitory control abilities and language skills could contribute to younger preschoolers' tendencies to exhibit a yes bias (see also Moriguchi, Okanda, & Itakura, 2008;Okanda & Itakura, 2007): young preschoolers might exhibit a yes bias automatically because they cannot inhibit a ''yes'' response or because they do not understand the context of the questions. For older preschoolers, Okanda and Itakura (2010b) suggested that there are more social reasons for choosing ''yes'' or ''no'' responses. In this study, we examined children's response latency to yes-no questions to provide support for the idea that younger and older preschoolers exhibit a yes bias due to different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations